2023
DOI: 10.9734/ijpss/2023/v35i132993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron and Panchagavya on Growth and Yield of Baby Corn (Zea mays L.)

Chanshim Molung Kanshouwa,
Biswarup Mehera

Abstract: The experiment was conducted in the Crop Research Farm, department of agronomy during the summer season of 2022 on baby corn crop. The treatments consisted of 3 levels of boron (2kg, 3kg, 4 kg/ha) and Panchagavya (2 sprays of 2%, 3%, 4%) as a foliar spray at 15 and 30 DAS and a control. The experiment was laid out in Randomized Block Design (RBD) with 10 treatments and replicated thrice. Application of Boron (4 kg/ha) and Panchagavya (2 sprays of 4%) produced maximum plant height (135.44 cm), plant dry weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…IAA and GA3 present in panchagavya which might have stimulated the production of growth regulators in cell system. Similar results was reported by Sreethu and Singh [13,19]. .…”
Section: Seed Yield (T/ha)supporting
confidence: 91%
See 1 more Smart Citation
“…IAA and GA3 present in panchagavya which might have stimulated the production of growth regulators in cell system. Similar results was reported by Sreethu and Singh [13,19]. .…”
Section: Seed Yield (T/ha)supporting
confidence: 91%
“…Similar results was reported by Reddy et al [12] in Finger millet. Further increase in plant dry weight with application of panchagavya 4% might be due to the supply of all micro and macronutrients and growth enzymes present in the panchagavya which favoured rapid cell division and multiplication with respect to Panchagavy-a, ammonia and nitrite oxidizers were found to colonize the leaves and increased the uptake and total N. Simlar results was reported by Sreethu and singh [13].…”
Section: Plant Dry Weight (G)mentioning
confidence: 68%
“…Kumar et al [34] found that treatment B3 (100 ppm) + Si3 (700 ppm) significantly increased plant height. Another study also reported that application of B (4 kg/ha) and Panchagavya (2 sprays of 4%) produced maximum plant height [37]. On the other hand, Dawson found T9 with foliar application of (90 ppm) B (1.5%) recorded higher plant height [43].…”
Section: Mm) On Root Mass Showing: Grams Fresh Weight Of Root (A) Num...mentioning
confidence: 90%
“…Treatment with B at 4 kg/ha and Panchagavya at 4% produced maximum plant height, plant dry weight, number of cobs per plant, cob yield with and without husk, and green fodder yield [34]. Another study found that foliar application of B at 0.3% resulted in significantly higher growth parameters such as plant height, plant dry weight, and crop growth rate, as well as yield attributes like number of cobs per plant, number of grains per cob, and grain yield [37]. Additionally, the foliar application of B at 0.6% along with zinc and iron increased plant height, plant dry weight, crop growth rate, number of leaves per plant, number of cobs per plant, and grain yieid [38].…”
Section: Different Methods Of Boron Applicationmentioning
confidence: 97%
See 1 more Smart Citation